Identification and Characterization of MAPK Signaling Pathway Genes and Associated lncRNAs in the Ileum of Piglets Infected by Clostridium perfringens Type C. (13th August 2020) - Luo, Ruirui; Huang, Xiaoyu; Yan, Zunqiang; Gao, Xiaoli; Wang, Pengfei; Yang, Qiaoli; Wang, Wei; Xie, Kaihui; Gun, Shuangbao
Abstract : Clostridium perfringens type C ( C. perfringens type C) is one of the main microbial pathogens responsible for piglet diarrhea worldwide, causing substantial economic losses for pig-rearing industries. The mitogen-activated protein kinase (MAPK) signaling pathway is a key regulator of inflammatory bowel disease, especially necrotic enteritis. However, whether and how the MAPK signaling pathway is involved in regulating the process of piglet diarrhea when challenged by C. perfringens type C are still unknown. Here, we screened 38 differentially expressed genes (DEGs) in piglets' ileum tissues experimentally infected with C. perfringens type C that were enriched in the Sus scrofa MAPK signaling pathway, based on our previous transcriptome data. Of these DEGs, 12 genes ( TRAF2, MAPK8, and GADD45G, among others) were upregulated whereas 26 genes ( MAPK1, TP53, and CHUK, among others) were downregulated in the infected group. Our results showed that MAPK1, TP53, MAPK8, MYC, and CHUK were in the core nodes of the PPI network. Additionally, we obtained 35 lncRNAs from the sequencing data, which could be trans -targeted to MAPK signaling pathway genes and were differentially expressed in the ileum tissues infected with C. perfringens . We used qRT-PCR to verify the expression levels of genes and lncRNAs related to the MAPK signaling pathway; their expression patterns were consistent with RNA sequencing data. Our results provide strong support for deeply exploring the role of the MAPK signaling pathway in diarrhea caused by C. perfringens type C.